2001
DOI: 10.1046/j.1440-1827.2001.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyrocyte integration, and thyroid folliculogenesis and tissue regeneration: Perspective for thyroid tissue engineering

Abstract: The thyroid gland is composed of many ball-like structures called thyroid follicles, which are supported by the interfollicular extracellular matrix (ECM) and a capillary network. The component thyrocytes are highly integrated in their specific structural and functional polarization. In conventional monolayer and floating culture systems, thyrocytes cannot organize themselves into follicles with normal polarity. In contrast, in 3-D collagen gel culture, thyrocytes easily form stable follicles with physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 140 publications
(195 reference statements)
0
26
1
Order By: Relevance
“…Thyrocytes within the follicles concentrated in the central zone may be subjected to a growth-inhibitory mechanism such as contact inhibition of cell growth, whereas thyrocytes within the follicles dispersed in the peripheral part may escape from such inhibitory regulation. As this issue is crucial for thyroid tissue regeneration or engineering (Toda et al 2001), further studies are in order. In addition, our study demonstrated that neogenic follicles rarely had C cells; and that C cells showed no proliferative ability.…”
Section: Discussionmentioning
confidence: 99%
“…Thyrocytes within the follicles concentrated in the central zone may be subjected to a growth-inhibitory mechanism such as contact inhibition of cell growth, whereas thyrocytes within the follicles dispersed in the peripheral part may escape from such inhibitory regulation. As this issue is crucial for thyroid tissue regeneration or engineering (Toda et al 2001), further studies are in order. In addition, our study demonstrated that neogenic follicles rarely had C cells; and that C cells showed no proliferative ability.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate thyroid biology, monolayer and floating culture systems have been developed and widely used [2][3][4][5]. These methods have facilitated thyroid biology.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have facilitated thyroid biology. However, the conventional methods, in which thyrocytes are unable to organize follicle structures, cannot satisfactorily provide thyrocytes with normal cellular integration [2][3][4][5]. In contrast, three-dimensional (3-D) collagen gel culture system allows thyrocytes to achieve follicle structures with their physiological polarity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations